2017
DOI: 10.1111/nmo.13238
|View full text |Cite
|
Sign up to set email alerts
|

Dietary therapies for functional bowel symptoms: Recent advances, challenges, and future directions

Abstract: Background: Functional gastrointestinal symptoms in irritable bowel syndrome (IBS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
81
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(85 citation statements)
references
References 170 publications
(429 reference statements)
1
81
0
3
Order By: Relevance
“…41 In studies reporting improved symptoms following the low-FODMAP diet, abdominal pain, gas and/or bloating are most often the symptom types with response. 1 Additionally, MRI studies have shown increased colonic gas associated with consumption of inulin (a fructan used as a prebiotic) both in healthy volunteers and patients with IBS. 7 The primary mechanisms proposed to support the reductions in abdominal pain, bloating and gas, are the reduction in substrates available for colonic fermentation and hence reduced gas production.…”
Section: Sorbitol Mannitolmentioning
confidence: 99%
See 1 more Smart Citation
“…41 In studies reporting improved symptoms following the low-FODMAP diet, abdominal pain, gas and/or bloating are most often the symptom types with response. 1 Additionally, MRI studies have shown increased colonic gas associated with consumption of inulin (a fructan used as a prebiotic) both in healthy volunteers and patients with IBS. 7 The primary mechanisms proposed to support the reductions in abdominal pain, bloating and gas, are the reduction in substrates available for colonic fermentation and hence reduced gas production.…”
Section: Sorbitol Mannitolmentioning
confidence: 99%
“…1 The combination of five subgroups of specific poorly absorbed and rapidly fermented carbohydrates-fructans, galactooligosaccharides, lactose, excess fructose and polyols-are thought to trigger gastrointestinal symptoms and are referred to by the collective term "FODMAP" ( Table 1) include single food avoidance and exclusion diets (eg a low-FODMAP diet)". 1 The combination of five subgroups of specific poorly absorbed and rapidly fermented carbohydrates-fructans, galactooligosaccharides, lactose, excess fructose and polyols-are thought to trigger gastrointestinal symptoms and are referred to by the collective term "FODMAP" ( Table 1) include single food avoidance and exclusion diets (eg a low-FODMAP diet)".…”
Section: Introductionmentioning
confidence: 99%
“…Регулярно обновляемые систематические обзоры новейших исследований терапии СРК указывают на то, что одним из наиболее многообещающих направле-ний является коррекция нарушений микробиоты путем диетических интервенций [31]. В поисках еще неизвестных звеньев патогенеза СРК исследо-ватели проявляют все больше интереса к изучению зависимости между рационом питания и функци-ональными симптомами заболевания.…”
unclassified
“…There has been a dramatic increase in the use of diet therapies for the management of functional bowel disorders, particularly irritable bowel syndrome . These include diets such as the NICE (National Institutes for Clinical Excellence) guidelines, gluten‐free diets and diets restricting food constituents such as capsaicin ; however, diets low in fermentable carbohydrates have received the greatest attention over recent years. FODMAPs refer to fermentable oligosaccharides (fructans, galacto‐oligosaccharides), disaccharides (lactose), monosaccharides (excess fructose) and polyols (e.g.…”
mentioning
confidence: 99%
“…Although the low FODMAP diet is increasingly embraced by physicians, dietitians and patients alike, there are ongoing questions regarding the magnitude of the benefit, the inability to identify patients most likely to respond, and the lack of understanding about the pathophysiology and mechanisms, as well as the safety implications . To assist in addressing these concerns, the editors of two leading journals in the area, Neurogastroenterology and Motility and the Journal of Human Nutrition and Dietetics , have assembled key papers in a single virtual issue, and all are available via open access.…”
mentioning
confidence: 99%